Physicochemical Properties of Bottom Sediments in Maruba Dam Reservoir, Machakos, Kenya - Allois Luvai; John Obiero; Christian Omuto (Applied and Environmental Soil Science)
Bottom sediments form an integral part of the aquatic ecosystem, where they serve as important sinks for contaminants. However, management options for bottom sediments require an analysis of the physical and chemical properties. Therefore, the aim of this study was to assess the physicochemical properties of bottom sediments in the Maruba dam reservoir in order to inform their potential use. The bottom sediments were obtained from three sampling points using a vibe-coring device. The samples were analyzed for grain size, sediment bulk density, pH, electrical conductivity, organic matter content, and nutrient content (nitrogen, phosphorous, and potassium) using standard laboratory procedures. The results of the study revealed that the bottom sediments were predominantly clay (56%). The mean pH value of the sediments was 6.63, which was found to be slightly acidic. The concentration of cations and anions in the bottom sediments was found to be quite high, with a mean value of 0.225 dS⋅m−1. The bottom sediments in the reservoir were found to be quite rich in the organic matter content (2.10%) and had a mean bulk density of 0.620 g·cm−3. The macronutrients (nitrogen, potassium, and phosphorous) had mean values of 0.12%, 0.46%, and 12.81 mg·kg−1, respectively. The study established that finely grained particles together with organic matter had a potential effect on the availability of macronutrients in bottom sediments. The concentration of the macronutrients of the bottom sediments evaluated in this study points to their potential use in agricultural activities or even in land reclamation.